2019
DOI: 10.1039/c9ra03557e
|View full text |Cite
|
Sign up to set email alerts
|

Study of the reaction of ninhydrin with tyrosine in gemini micellar media

Abstract: The importance of the study increased due to the use of a very small quantity of gemini surfactant required to perform the reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 48 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…The study deals with the synthesis and characterization of gemini surfactants and their influence on the kinetic behavior of ninhydrin with zinc-glycylleucine. The reason for choosing this particular study is the mechanism of ninhydrin with amino acids reaction in water, conventional surfactants (CTAB, cetylpyridinium bromide, CPB) and the various solvent medium is well recognized [24][25][26][27][28][29][30]59 . Under the identical reaction condition, it was found that the study was catalyzed and accelerated quite enough in gemini surfactants (below their cmc value) than aqueous medium 73 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study deals with the synthesis and characterization of gemini surfactants and their influence on the kinetic behavior of ninhydrin with zinc-glycylleucine. The reason for choosing this particular study is the mechanism of ninhydrin with amino acids reaction in water, conventional surfactants (CTAB, cetylpyridinium bromide, CPB) and the various solvent medium is well recognized [24][25][26][27][28][29][30]59 . Under the identical reaction condition, it was found that the study was catalyzed and accelerated quite enough in gemini surfactants (below their cmc value) than aqueous medium 73 .…”
Section: Discussionmentioning
confidence: 99%
“…Ninhydrin reactions are one of the most fundamental and biochemical studies. Ninhydrin, a chemical reagent, is used enormously for detection of amine functional group wherein it reacts with an amino group and generates diketohydrindylidene-diketohydridamine (DYDA) [22][23][24][25][26][27][28][29][30] . The color of the product formed between the reaction of ninhydrin and amino acids disappears at room temperature, several efforts were performed towards the stability of products that include the formation of the metal complex with amino acids, change of solvent, presence of conventional monomeric surfactant 28,[31][32][33] .…”
mentioning
confidence: 99%
“…By using these results, different activation parameters were calculated by linear least-squares regression procedure. The mechanism of amino acids with ninhydrin has received great attention of researchers/investigators due to the use in different fields [47][48][49][50][51]. The proposed mechanism for the current study of ninhydrin and histidine is demonstrated in scheme 1.…”
Section: Effect Of Several Parameters On K ψmentioning
confidence: 99%
“…In an aqueous medium, a surfactant can form aggregates at a certain concentration due to a delicate balance of hydrophilic interactions and hydrophobic interactions. 1 This surfactant aggregate is known as a micelle, and the concentration at which a surfactant micelle formed is known as cmc. [2][3][4] This micellar aggregation of an amphiphilic substance can augment the solubility of weakly soluble organic compounds by altering their microenvironment properties e.g.…”
Section: Introductionmentioning
confidence: 99%